Painful diabetic neuropathy is associated with increased nerve regeneration in patients with type 2 diabetes undergoing intensive glycemic control - Ponirakis, Georgios; Abdul‐Ghani, Muhammad A; Jayyousi, Amin; Zirie, Mahmoud A; Qazi, Murtaza; Almuhannadi, Hamad; Petropoulos, Ioannis N; Khan, Adnan; Gad, Hoda; Migahid, Osama; Megahed, Ayman; Al‐Mohannadi, Salma; et al. (Journal of diabetes investigation, 2021)
Aims/Introduction Painful diabetic peripheral neuropathy (pDPN) is associated with small nerve fiber degeneration and regeneration. This study investigated whether the presence of pDPN might influence nerve regeneration in patients with type 2 diabetes undergoing intensive glycemic control. Materials and Methods This exploratory substudy of an open‐label randomized controlled trial undertook the Douleur Neuropathique en 4 questionnaire and assessment of electrochemical skin conductance, vibration perception threshold and corneal nerve morphology using corneal confocal microscopy in participants with and without pDPN treated with exenatide and pioglitazone or basal–bolus insulin at baseline and 1‐year follow up, and 18 controls at baseline only. Results Participants with type 2 diabetes, with (n = 13) and without (n = 28) pDPN had comparable corneal nerve fiber measures, electrochemical skin conductance and vibration perception threshold at baseline, and pDPN was not associated with the severity of DPN. There was a significant glycated hemoglobin reduction (P < 0.0001) and weight gain (P < 0.005), irrespective of therapy. Participants with pDPN showed a significant increase in corneal nerve fiber density (P < 0.05), length (P < 0.0001) and branch density (P < 0.005), and a decrease in the Douleur Neuropathique en 4 score (P < 0.01), but no change in electrochemical skin conductance or vibration perception threshold. Participants without pDPN showed a significant increase in corneal nerve branch density (P < 0.01) and no change in any other neuropathy measures. A change in the severity of painful symptoms was not associated with corneal nerve regeneration and medication for pain. Conclusions This study showed that intensive glycemic control is associated with greater corneal nerve regeneration and an improvement in the severity of pain in patients with painful diabetic neuropathy. There has been a resurgence of interest in identifying new drug targets or, predictive biomarkers of disease‐modifying therapies in diabetic neuropathy. We show that the presence of painful diabetic neuropathy was associated with greater corneal nerve regeneration and an improvement in painful neuropathic symptoms in patients with type 2 diabetes undergoing intensive glycemic control.